2015
DOI: 10.1038/tpj.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Role of SLC22A1 polymorphic variants in drug disposition, therapeutic responses, and drug–drug interactions

Abstract: The SCL22A1 gene encodes the broad selectivity transporter hOCT1. hOCT1 is expressed in most epithelial barriers thereby contributing to drug pharmacokinetics. It is also expressed in different drug target cells, including immune system cells and others. Thus, this membrane protein might also contribute to drug pharmacodynamics. Up to 1000 hOCT1 polymorphisms have been identified so far, although only a small fraction of those have been mechanistically studied. A paradigm in the field of drug transporter pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 102 publications
0
35
0
Order By: Relevance
“…Although imatinib does not seem to be translocated by human OCT1 (Nies et al, 2014), the polymorphic variants of OCT1 have been several times reported to affect outcome in the treatment of chronic myeloid leukemia (CML). This apparent controversy between human OCT1 polymorphic variants and outcomes of treatment with imatinib has been recently again confirmed in other studies (Angelini et al, 2013;Arimany-Nardi et al, 2015;Crossman et al, 2005). Drugs such as morphine, analgesic drug tramadole metabolite O-desmethyltramadol, and antiemetic drugs tropisetron and ondasetron have also been shown in pharmacogenetic clinical studies to be affected by OCT1 variants (Arimany-Nardi et al, 2015).…”
Section: Clinical Significance Of Oct1 Transporter and Its Genetic Vamentioning
confidence: 93%
See 3 more Smart Citations
“…Although imatinib does not seem to be translocated by human OCT1 (Nies et al, 2014), the polymorphic variants of OCT1 have been several times reported to affect outcome in the treatment of chronic myeloid leukemia (CML). This apparent controversy between human OCT1 polymorphic variants and outcomes of treatment with imatinib has been recently again confirmed in other studies (Angelini et al, 2013;Arimany-Nardi et al, 2015;Crossman et al, 2005). Drugs such as morphine, analgesic drug tramadole metabolite O-desmethyltramadol, and antiemetic drugs tropisetron and ondasetron have also been shown in pharmacogenetic clinical studies to be affected by OCT1 variants (Arimany-Nardi et al, 2015).…”
Section: Clinical Significance Of Oct1 Transporter and Its Genetic Vamentioning
confidence: 93%
“…In these individuals carrying SLC22A1 polymorphisms, significantly higher glucose levels after metformin treatment have been associated with higher AUC and C max for metformin (Shu et al, 2007(Shu et al, , 2008. In patients with type II diabetes mellitus, only genetic variation rs622342 has been associated with the glucose-lowering effect of metformin (Becker et al, 2009), although there also exist controversial reports (Arimany-Nardi et al, 2015). Similarly, polymorphism rs622342 A > C has been shown to be associated with poorer drug response to antiparkinson drug levodopa (Becker et al, 2011).…”
Section: Clinical Significance Of Oct1 Transporter and Its Genetic Vamentioning
confidence: 97%
See 2 more Smart Citations
“…For example, pentamidine is transported within the body by human OCT1, a broad selectivity transporter encoded by the highly polymorphic SCL22A1 gene, 117, 118 variants of which affect the efficiency of uptake, distribution, and excretion of clinically relevant drugs. 117, 119, 120 Furthermore, CYP450 enzymes with roles in the metabolism of pentamidine include CYP1A1, CYP1A2, CYP2C8, CYP2C19, CYP2B6, CYP3A4, CYP3A5 and CYP4A11. 81 …”
Section: Introductionmentioning
confidence: 99%